FP_Tree Patterns of Using Social Media (Social Media) in E-Commerce Transactions - Lismardiana Sembiring; Anjar Pinem; Jimmy Perangingangin (SEAN Institute, 2023)
The needed for the general public to shop online through e-commerce has become a trend since the start of Covid-19. Social media has become a daily meal for the general public, from teenagers to parents and even the elderly, on average they already have an account and are fluent in social media, even an individual can have two or three social media accounts such as; Instagram,Facebook,Tiktok and Twitter. Of all people in Indonesia who have used social media, on average they have shopped online.Several research have also done the FP_Growth method and the Rule Mining Association in increasing sales turnover and marketing products using social media. The FP_Growth concept and the Rule mining association will produce a prequent item or set item in online shopping transactions using social media accounts.From the results of the prequent item or set item in online shopping transactions, the purpose to determine the mapping pattern of using social media in online shopping. This is useful as a reference for B2B, B2C, C2C, C2B e-commerce to increase the sales turnover of their e-commerce products by developing an electronic marketing strategy so that they are able to compete with other e-commerce actors. The mapping pattern has a min support group of 22% (A4, A5, D4, D6); 30% (A4, A5, D4, D6, A7, B4, B7), a group of 60% min support (A6, B5, B6, C7, D7,C6) and min group conf 27%(A6,B5,B6,C7,D7);38%(C6); conf 16%(A7,B4,B7)